PENGARUH PROMOSI, KUALITAS PELAYANAN DAN PENGETAHUAN TERHADAP MINAT MASYARAKAT BERINVESTASI LOGAM MULIA DI PEGADAIAN SYARIAH LANGSA BARAT. - Guspia Ningsih , Guspia Ningsih; Dayyan, Muhammad; Nurjanah , Nurjanah; Meylianda (Fakultas Ekonomi dan Bisnis Islam, 2019)
The purpose of this research that to knowing the promotion effect, service quality and knowledge of people willingness in precious metal investation at Unit Pegadaian Syariah, West Langsa and to knowing percial effect and simultance of people willingness in precious metal investation. This research using quantitative analysis to collect the data, utilized 85 respondents as research samples, this samples of research took by doing nonprobability sampling with quota sampling method, which is the sample taking by using the element of population technic based on researcher consideration and the number of samples had been determined. In collecting data was using questioner technic about 16 questions which rate from 1-5 Likert scale and examined the expedience by utilized the validity and reliability. The data have been collected by examined classic assumption including normality, linearity, multicollinearity, heteroscedasticity and autocorrelation test, after that analyzed by using double regression analyses and hypothesis test of T test (parcial) F test (simultance) and determinant (RÂ²). according to the hypothesis test in significance level there are 5% parcial showed that (1) there is positive effect and significance promotion of people to invest precious metal at Unit Pegadaian Syariah, West Langsa (2) there is positive effect and significance service quality in people willingness to invest the precious metal at Unit Pegadaian Syariah, West Langsa (3) there is positive effect and significance knowledge of people interest to invest the precious metal at Unit Pegadaian Syariah, West Langsa. Then in simultance promotion have the positive effect of service quality and knowledge. Moreover, have significance willingness of the people to invest precious metal at Unit Pegadaian Syariah, West Langsa. In the other hand the coefficient of determinant (RÂ²) result about 0,655, it means contribute of the independent variables (promotion, service quality, and knowledge) influence dependent variables (willingness of precious metal investation) about 65,5% but 34,5% influence by other variables.